Recovery and grading of goat oocytes with special reference to laparoscopic ovum pick-up technique: a review - Abdullah, Ramli; Wan-Khadijah, W.E.; Rahman, A.N.M.A. (2011)
Oocytes are the main raw materials for in vitro embryo production (IVP) experiments. Therefore, the success of any IVP program in goat production, either in vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) largely depends on the continuous supply of quality oocytes in optimum quantity. A number of methods are currently used for oocyte recovery (OR) from live or slaughtered goats. Although, abattoir is the most easy and cheapest source of oocytes, however, in certain countries especially in Malaysia, abattoir source is extremely limited due to low slaughtering activities as a consequence of shortage of breeding stock. In Malaysia normally older goats or goats those are culled for breeding are slaughtered for meat. Therefore, the quality of oocytes recovered from ovaries of these goats is generally lower. On the contrary, OR from live goats using laparoscopic ovum pick-up (LOPU) technique provides many advantages, for example, OR can be repeated 3-5 times in the same goat at interval as short as a week or less, OR can be done in prepubertal and aged goats, if prepubertal goat is used for OR then generation intervals will be reduced, LOPU coupled with IVP can become an efficient method of early propagation of valuable goats and LOPU can overcome limitations frequently associated with multiple ovulation-embryo transfer (MOET). Therefore, LOPU can be an alternative and efficient OR method in goat not only for Malaysia but also for other countries. The current study will discuss oocyte recovery methods with special reference to LOPU and grading of recovered oocytes in goats. © 2011 Asian Network for Scientific.Information.